During the Covid-19 Pandemic, Marketing Strategy Analysis for Crispy MSMEs "MA ICIH" - D. Yadi Heryadi; Fachrurazi Fachrurazi; Ita Nurcholifah; Muhammad Yusuf (Jurnal Publikasi Ilmu Manajemen, 2023)
Large-scale social restrictions (PSBB) cause conventional marketing of company products to be limited. The purpose of this study was to examine the impact of the marketing approach during the Covid-19 pandemic on the performance of MSMEs with technology as a moderator variable with the research subject being Kripik "Ma Icih" MSME customers. MSMEs during the pandemic must be able to carry out product marketing using social media applications. A sample of 100 respondents became the sample of this study. The data collection approach has been tested for validity and reliability by reporting, interviews, and questionnaires. The results showed that: (1) With a value of 0.767 and a P-value of 0.0033, the effect of production on MSME performance is positive and significant. (2) With a result of 0.000<0.05, technology moderates the impact of production on MSME performance in a positive and significant way. (3) Production on MSME performance is positive and significant with a value of 0.468 and a P-Value of 0.042 (4) The positive and significant distribution of MSME performance moderated by technology shows a result of 0.030 <0.05 (5) There is a positive and significant difference between direct marketing and MSME performance with a value of 0.265 and a P-Value of 0.000. (6) the positive and significant effect of direct marketing on the performance of MSMEs moderated by technology shows a result of 0.000 <0.05.